Westonci.ca is the best place to get answers to your questions, provided by a community of experienced and knowledgeable experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.

(x+3)^2 = x^2-3(1-x)

Sagot :

(x+3)(x+3) = x^2 -3 + 3x
x^2 + 3x + 3x + 9 = x^2 + 3x - 3
x^2 + 6x + 9 = x^2 + 3x - 3
6x + 9 = 3x - 3
3x + 9 = -3
3x = -12
x = -4

Check:
(-4+3)^2 = (-4)^2 - 3(1+4)
(-1)^2 = 16 - 3(5)
1 = 16-15
1 = 1 :)